2 - Firmes transnationales, institutions financières internationales et la crise économique et sociale de l’Afrique - Abdoulaye DIAGNE (Africa Development, 1985)
In this paper, the author is looking at the role which Transnational Corporations (TNCs) and International Financial Institutions (IFI) played in the social and economic crisis Africa is facing. In his introduction, he already argues that, although external factors are said to be the major causes of the crisis, one should also consider the role played by internal factors. He also mentions that quantitative data are not enough to assess the role of these institutions. He then gives an overview of the extent of the crisis in Africa before considering the importance of the crisis in some sectors such as agriculture, industry, external relations. This, he assumes, gives a clear picture of the specific roles the external factors played in the economic and social crisis of the continent. He finally argues that the major résultats of the involvement of the IFI in the economy of our countries are an accelerated pauperization, the violent introduction of savage liberalism and a tighter integration of our countries in the International Division of Labour.